First case in Italy of acquired resistance to oseltamivir in an immunocompromised patient with influenza A/H1N1v infection. - Campanini, Giulia; Piralla, Antonio; Rovida, Francesca; Puzelli, Simona; Facchini, Marzia; Locatelli, Franco; Minoli, Lorenzo; Percivalle, Elena; Donatelli, Isabella; Baldanti, Fausto (J Clin Virol, 2010)
A pandemic influenza A/H1N1v strain with the neuraminidase H274Y mutation was detected in nasal secretions of a 2-year-old leukemic patient with influenza-like illness after 18 days of treatment with oseltamivir. At baseline, no drug-resistant virus was found, while 4 days after treatment initiation a mixture of wild-type and mutated virus was detected. After treatment interruption, the wild type influenza virus re-emerged and became prevalent in nasal secretions after a few days, suggesting the lower fitness of the mutated virus strain. The patient slowly improved concurrently with a decrease in virus load, which resulted negative 42 days after diagnosis. No other drug-resistant influenza A/H1N1v virus strains have been detected in Italy (up to the end of November 2009) since the first case of the novel A/H1N1v virus was identified in the country (May 2009).
Keywords: Amino Acid Substitution; Antiviral Agents; Bodily Secretions; Child, Preschool; Drug Resistance, Viral; Female; Humans; Immunocompromised Host; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Molecular Sequence Data; Mutation, Missense; Neuraminidase; Nose; Oseltamivir; RNA, Viral; Sequence Analysis, DNA; Treatment Outcome; Viral Load; Viral Proteins; Withholding Treatment